Anthroponyms in Lower Imereti (According to Ocribian Speech) - Dadiani, Eka (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2023)
This article explores the formation and word structure of anthroponyms in sub- Imerian, specifically Ocribian speech. The analysis is based on dialectal material preserved at the Tariel Futkaradze Scientific-Research Center of Kartveloology, recorded in the 1990s in villages of the Okrib community (Orpiri, Kursebi, Chkepi). 1. In Ocribian speech, proper nouns with a consonant base predominantly exhibit names ending in -i vowels: Tarasi-m, Jimsheri-m, Nodari-s, Emzari-s... These are alternated with forms ending in -o (Gramiton-o, Eter-o). Conversely, a less common trend reverses this pattern, producing names ending in -i from consonant-based forms; for instance, St. Georg-o appears in spell texts. Both trends emerge from Georgian soil and exemplify the internal linguistic development laws (dialect) (K. Kublashvili). A peculiarity is noted in names ending with -a vowel, which are represented with an -e ending: Juliete, Natele. 2. Anthroponyms are formed using word-forming affixes: -A: Gramitona, Razdena... Ciuria, Endings such as -a > -e: Triphone, Tariele. -ia: Tengizia, Razdenia... Shotaia, Kakoia. -ia > -ie (partial assimilation): kikilie, datoie. Rarely -ia > -ii (complete assimilation): as seen in the case of Lashi. Names like Ik-o: Valiko, Datiko; -ik-a / -uk-a: Ivanika, Beruka; -un-a: Datuna; -el-a / -il-e (>-il-a): Kaciela. -il-o in words such as Kikilo, Babilo; -Oul: Shotouli; -Uts-A: Gogutsa, Tsutsa. 3. Interesting phonetic changes in some proper names include: Noah > No-v-e (development of v sound), Ieso > Iose (metathesis), Margarita < Margalita (dissimilation). 4. Ocribian speech notably includes a considerable usage of proper names of Russian origin or influence: Sonichka, Anichka, Alyosha, Shura, Zhora... 5. Written texts also feature various names and nicknames: Alim, Apoli, Bululi, Bujgi, Mastredia, Mironia... The primary tendencies in the evolution of anthroponyms in Ocribian speech are consistent with Georgian norms, with differences primarily observed in individual names that adhere to general rules.